Safety and efficacy of Levucell® SB (Saccharomyces cerevisiae CNCM I‐1079) as a feed additive for all pigs. (16th January 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of Levucell ® SB when used in feed for suckling piglets, pigs for fattening and minor porcine species. Levucell ® SB is the trade name for a feed additive based on viable cells of a strain Saccharomyces cerevisiae currently authorised as a zootechnical additive for weaned piglets, sows, chickens for fattening and minor poultry species for fattening. The applicant is now seeking authorisation as a zootechnical additive for use with all pigs. In the context of a previous opinion, the identity of the strain was confirmed, and according to the Qualified Presumption of Safety (QPS) approach to safety assessment, it was presumed safe for the target species, consumers of products from animals fed the additive and the environment. Since no concerns are expected from other components of the additive, Levucell ®  SB is also considered safe for the target species, including all pigs, consumers and the environment. Levucell ® is not a skin or eye irritant or a skin sensitiser. Inhalation exposure is unlikely. Encapsulation used in the existing coated forms is not expected to introduce hazards for users. In previous opinions, Levucell ® SB was found to have the potential to be efficacious in sows and weaned piglets at the dose of 1 × 10 9  colony forming units (CFU)/kg complete feedingstuffs. Since the dose proposed for use with all pigs is the same as that demonstrated to be effective in weaned piglets and sows, and it can be reasonably assumed that the mode of action is the same, the conclusion on efficacy for weaned piglets and sows can be extrapolated to all pigs. Therefore, the FEEDAP Panel concludes that Levucell ®  SB has the potential to be efficacious in all pigs at 1 × 10 9  CFU/kg feedingstuffs.